Determinants of Serum Polybrominated Diphenyl Ether (PBDE) Levels among Pregnant Women in the CHAMACOS Cohort - Castorina, Rosemary (2011)
[Image: see text] We measured levels of 10 polybrominated diphenyl ether (PBDE) congeners in serum collected during pregnancy and at delivery from 416 pregnant, predominantly immigrant, women living in Monterey County, CA. The most frequently detected congeners were BDE-47, -99, -100, and -153, all components of the penta mixture, detected in >97% of samples. We used multivariable regression models to examine factors associated with exposure to individual PBDE congeners as well as their total summed concentration (ng/g lipid). Prenatal and delivery total PBDE levels were correlated between sampling times (n = 21; Pearson r = 0.99, p < 0.001). In multivariable models, total PBDE levels increased significantly with time residing in the U.S. (p < 0.001) and among women with ≥3 pieces of stuffed furniture in their homes (p < 0.05). Women’s total PBDE levels increased 4.0% (95% CI = 2.8, 5.3) for each additional year residing in the U.S., after adjustment for prepregnancy BMI, weight gain during pregnancy, and SES. Having ≥3 pieces of stuffed furniture in the home was associated with a 26.8% (95% CI = 2.0, 57.5) increase in women’s serum PBDE levels. Findings suggest PBDE indoor contamination in California homes is contributing to human exposures in a population of recent immigrants.